2020
DOI: 10.1016/j.ccc.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin

Abstract: Procalcitonin (PCT) is a protein that consists of 116 amino acids and is the peptide precursor of calcitonin. Calcitonin is initially biosynthesized as PCT which under normal conditions, is found in low levels in the circulation (≤ 0.1 ng/mL). 12 PCT was first described as a marker of bacterial infection in 1993 when high concentrations of calcitonin-like immunoreactivity were detected in the blood of patients with extra-thyroid diseases. 3 Using a monoclonal immunoradiometric assay for calcitonin precursors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 91 publications
0
47
0
1
Order By: Relevance
“…A reduction in serum prealbumin concentrations typically indicates the presence of acute inflammation and/or malnutrition, unlike other biomarkers such as CRP and procalcitonin which predominantly reflect the inflammatory burden (42)(43)(44). Its relatively short half-life makes it a suitable marker to assess and monitor rapid changes inflammatory burden and nutritional state.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in serum prealbumin concentrations typically indicates the presence of acute inflammation and/or malnutrition, unlike other biomarkers such as CRP and procalcitonin which predominantly reflect the inflammatory burden (42)(43)(44). Its relatively short half-life makes it a suitable marker to assess and monitor rapid changes inflammatory burden and nutritional state.…”
Section: Discussionmentioning
confidence: 99%
“…Another protein that can serve as an inflammatory marker is PCT, a peptide precursor of calcitonin that consists of 116 amino acids. Calcitonin is initially biosynthesised as PCT, which, under normal conditions, is found in low levels in the circulation [ 19 ]. PCT viral infection may be released under the action of proinflammatory mediators such as IL-6, TNF release or the like, which leads to elevated levels of peripheral blood [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of PCT indicates bacterial infection, while the elevation of CRP indicates inflammation in the body. 12 It could be observed from Table 2 that there were no significant differences in the proportions of patients with abnormal PCT and CRP among the three groups (P > .05). This indicated that PCT and CRP were lowly correlated with the disease severity of COVID-19.…”
Section: Comparison Of Blood Routine and Other Pneumonia-related Blmentioning
confidence: 81%